Fractal dimension algorithm for detecting oil spills using RADARSAT-1 SAR - Marghany, Maged; Hashim, Mazlan; Cracknell, Arthur P. (Springer Berlin / Heidelberg, 2007)
This paper introduces a method for modification of the formula of the fractal box counting dimension. The method is based on the utilization of theprobability distribution formula in the fractal box count. The purpose of this method is to use it for the discrimination of oil spill areas from the surrounding features e.g., sea surface and look-alikes in RADARSAT-1 SAR data. The result shows that the new formula of the fractal box counting dimension is able to discriminate between oil spills and look-alike areas. The low wind area has the highest fractal dimension peak of 2.9, as compared to the oil slick and the surrounding rough sea. The maximum error standard deviation of low wind area is 0.68 which performs with fractal dimension value of 2.9.